Improper Planning Leading to Idling of Three Multi-Storeyed Buildings at RGGGH Chennai in Tamil Nadu - CAG of India (CAG of India)
Improper planning and failure to assess the actual requirements by RGGGH and DME led to idling of three structurally completed multi-storeyed buildings constructed at a cost of INR 55.33 crore thereby depriving critical care to the needy patients.